The effectiveness of giving silkworms Tubifex sp. enriched with curcumin on the growth and survival of jelawat fish larvae Leptobarbus hoevenii - Nur Asiah; Ayuningtyas Putri, Fadila; Heltonika, Benny (Jurnal Akuakultur Indonesia, 2026)
Curcumin is a secondary metabolite that enhances fish immunity and functions as an antibacterial and antimicrobial agent. Curcumin acts as a supplement to increase the larvae's appetite. The aim of this study was to evaluate the effect of curcumin-enriched silkworms (Tubifex sp.) on the growth and survival of jelawat fish larvae. This research was carried out in June–July 2023 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Sciences, Riau University. This study applied an experimental method using a completely randomized design (CRD) with three replications. The treatment in this study was P0 (silkworms without curcumin enrichment), P1 (silkworms enriched with curcumin 0.2 mg/kg silkworms), P2 (silkworms enriched with curcumin 0.3 mg/kg silkworms), P3 (silkworms enriched with 0.4 mg/kg curcumin), and P4 (silkworms enriched with curcumin 0.5 mg/kg silkworms). The results showed that the treatment of silkworms enriched with curcumin had a significant effect on the growth and survival of jelawat fish larvae (P<0.05). The best treatment is P3 (silkworms enriched with curcumin 0.4 mg/kg silkworms) with absolute weight growth of 2.26 ± 0.04 g, absolute length 5.25 ± 0.03 cm, SGR 11.84 ± 0.04% and survival 100 ± 0.00% respectively. The water quality parameters during the research period were temperature 27.2-29.5℃, pH 6.3-7.5, and dissolved oxygen 4.5-5.8 mg/L still in good condition for jelawat fish. Keywords: curcumin, jelawat fish larvae, silkworms   Abstrak Kurkumin merupakan salah satu senyawa metabolit sekunder yang dapat meningkatkan daya tahan tubuh ikan dan memiliki manfaat sebagai zat anti bakteri atau mikroba. Kurkumin berperan sebagai suplemen untuk menambah nafsu makan larva. Tujuan penelitian adalah untuk mengetahui pengaruh pemberian cacing sutera (Tubifex sp.) yang diperkaya kurkumin terhadap pertumbuhan dan kelulushidupan larva ikan jelawat. Penelitian ini dilaksanakan pada bulan Juni–Juli 2023 di Laboratorium Pembenihan dan Pembibitan Ikan Fakultas Perikanan dan Ilmu Kelautan Universitas Riau. Penelitian ini menggunakan metode eksperimen dengan rancangan acak lengkap faktor dan tiga kali ulangan. Perlakuan pada penelitian ini adalah P0 (cacing sutera tanpa diperkaya kurkumin), P1 (cacing sutera yang diperkaya dengan kurkumin 0,2 mg/kg cacing sutera), P2 (cacing sutera yang diperkaya dengan kurkumin 0,3 mg/kg cacing sutera), P3 (cacing sutera yang diperkaya dengan kurkumin 0,4 mg/kg cacing sutera), dan P4 (cacing sutera yang diperkaya dengan kurkumin 0,5 mg/kg cacing sutera). Hasil penelitian menunjukkan bahwa pemberian cacing sutera diperkaya kurkumin berpengaruh nyata terhadap pertumbuhan dan kelangsungan hidup larva ikan jelawat (P<0,05). Perlakuan terbaik adalah P3 (cacing sutera yang diperkaya dengan kurkumin 0,4 mg/kg cacing sutera) dengan pertumbuhan bobot mutlak 2,26 ± 0,04 g, panjang mutlak 5,25 ± 0,03 cm, SGR 11,84 ± 0,04% dan kelangsungan hidup 100 ± 0,00%. Parameter kualitas air selama penelitian yaitu suhu 27,2-29,5℃, pH 6,3-7,5, dan oksigen terlarut 4,5-5,8 mg/L, masih dalam kondisi baik untuk ikan jelawat. Kata kunci: cacing sutera, kurkumin, larva ikan jelawat